Evaluation of ammonia and odour emissions from animal slurry and digestate storage in the Po Valley (Italy). (15th February 2020) - Zilio, M.; Orzi, V.; Chiodini, ME.; Riva, C.; Acutis, M.; Boccasile, G.; Adani, F.
Graphical abstract: Highlights: The storage facilities for animal manure determine ammonia and odour emissions. These emissions cause environmental problems and annoyance to inhabitants. The determination of emission rates is useful to quantify these problems. Ammonia and odours have been detected studying four storage facilities during two years. Both ammonia and odour emitted depended upon slurries' characteristics and environmental parameters. Abstract: Ammonia and odour emissions from one lagoon (Lagoon 1: pig slurry) and three tanks (Tank 2: cow slurry; Tank 3: digestate from pig slurry and energy crops; Tank 4: digestate from pig and cow slurries plus energy crop) used for slurry storage were sampled for two years (2015–2017) in livestock farms that differed for animal breeding and manure management (anaerobic digestion). On average, the ammonia emission rate (AER) was higher for Tank 3 (AER of 30.68 ± 28.1 g N-NH3 m −2 d −1 ) than for Lagoon 1 and Tank 2 and 4, i.e. 9.29 ± 14.89 gN-NH3 m −2 d −1, 9.38 ± 13.75 g N-NH3 m −2 d −1, 15.74 ± 21.91 g N-NH3 m −2 d −1, respectively. PLS regression analysis (R 2 = 0.544; R 2 Adj. = 0.484) indicated that temperature was the main predictor of ammonia emitted, followed by concentration in the slurry of total ammonia and the relative percentage of volatile solids (VS). On the other hand, PLS analysis (R 2 = 0.529, R 2 adj. = 0.417) indicated that odour emissions from animal slurry storages depended similarly upon total solids and VS (both referred to fresh weight) slurry contents, TAN/TKN ratio and degrees of biological stability (measured by anaerobic biogas potential – ABP), resulting in the Specific Odours Emission Rates (SOER) of 12, 124 ± 7, 914 and 35, 207 ± 41, 706 OUE m −2 h −1, 65, 430 ± 45, 360 and 43, 971 ± 53, 350 OUE m −2 h −1, for Lagoon 1 and Tanks 2, 3 and 4. These results suggest covering the tanks to limit both ammonia and odour emissions.